Pacifist to Padre : The World War II Memoir of Chaplain Roland B. Gittelsohn, December 1941-January 1946 - Gittelsohn, Roland Bertram, 1910-1995 (Book collections on Project MUSE., 2020)
"Pacifist to Padre deftly threads so many elements of the World War II chaplaincy into a compelling and thoughtful narrative. It offers a personal window into a complex institution. It provides insight into the world of an unusual American space that has been naturalized as normal: of government-sponsored and managed religion. And it brings that world into focus from the vantage point of a man who never would have predicted pinning the Jewish chaplain's tablet insignia to his collar, a Jewish pacifist turned military padre"--